Knowledge, attitudes and risk perceptions towards Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV/AIDS) among health sciences students in a public university, Malaysia - Elkalmi, Ramadan Mohamed Mahmod; Al-Shami, Abdulkareem Mohammed; Alkoudmani, Ramez M.; Elsayed, Tarek Mohamed Ali; Al-lela, Omer Qutaiba B.; Patel, Isha (Indian Academy of Pharmacists (IAOP)., 2015)
Objectives: A cross-sectional study was conducted to investigate the level of knowledge, attitudes, and risk perceptions regarding human immunodeficiency virus (HIV) and acquired immunity deficiency syndrome (AIDS) among final year health sciences students in the International Islamic University Malaysia (IIUM), Kuantan, Malaysia. Methods: Students admitted in the schools of medicine, pharmacy, nursing, dentistry and allied health sciences at IIUM, Kuantan campus were targeted. Online questionnaire was completed by 236 of final students who volunteered to be a part of this study. Data were collected and analysed by using the Statistical Package for Social software (SPSS). Results: The vast majority of respondents were females (n=165, 70%). About 41.1% of participants were pharmacy students followed by medicine (n= 61, 25.8%), allied health sciences (n=40, 16.9%), nursing (n=20, 8.5%) and dentistry (n=18, 7.6%). Conclusion: The present study results showed moderate awareness about HIV/AIDS treatment, methods of HIV transmission, and educational knowledge of HIV/AIDS among students. The curriculum offered in different health professions should incorporate correct information about HIV/AIDS, thereby minimizing fear, misconceptions, and negatives attitudes that practising professionals hold about HIV/AIDS patients.